Beyond CD19: Opportunities for Future Development of Targeted Immunotherapy in Pediatric Relapsed-Refractory Acute Leukemia - Shalabi, Haneen; Angiolillo, Anne; Fry, Terry J. (Frontiers in Pediatrics, 2015)
Chimeric antigen receptor (CAR) T cell therapy has been used as a targeted approach in cancer therapy. Relapsed and refractory acute leukemia in pediatrics has been difficult to treat with conventional therapy due to dose limiting toxicities. With the recent success of CD 19 CAR in pediatric patients with B cell ALL, this mode of therapy has become a very attractive option for these patients with high risk disease. In this review, we will discuss current treatment paradigms of pediatric acute leukemia, and potential therapeutic targets for additional high risk populations, including T cell ALL, AML, and infant ALL.